PENGARUH KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN BANK MEGA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI - Kusumaningtyas, Intan -; Suddin, alwi - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT This study aims to analyze the significance of the effect of: (1) financial compensation to job satisfaction, (2) non-financial compensation to job satisfaction, (3) motivation to job satisfaction, (4) financial compensation moderated motivation to job satisfaction, (5) non-financial compensation are moderated by the motivation to work on job satisfaction of employees of Bank Mega Cluster Surakarta. Bank Mega Cluster employee population Surakarta October 2011 totaled 346 people. Random sample as many as 70 people. The data collection technique using a questionnaire through validity and reliability. Data analysis techniques using classical assumption test, multiple linear regression, and the absolute difference test. The results obtained by the analysis of (1) all of the variables proved valid questionnaires, (2) questionnaire questionnaire all variables proved reliable (3) test multikonolinearitas pass the test, pass the test heteroscedasticity test, autocorrelation test pass the test, pass the test and normality test. Conclusion of the study: (1) significant financial compensation to employee job satisfaction, (2) non-financial compensation significant effect on job satisfaction of employees, (3) motivation significant effect on job satisfaction, (4) financial compensation is not proven moderated by motivation (5) non-financial compensation is also not proven to be moderated by the motivation to work. Keywords: financial compensation, non-financial compensation, work motivation, job satisfaction.